Energy - Efficient IaaS-PaaS Co-Design for Flexible Cloud Deployment of Scientific Applications - Guyon, David; Orgerie, Anne-Cécile; Morin, Christine (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD); 2018: Anais do XXX International Symposium on Computer Architecture and High Performance Computing, 2018)
Reducing the massive amount of energy consumed by cloud datacenters becomes of major importance. In the usual approach where resources are consolidated into fewer servers in order to power down the others, it still remains periods of time when servers are not fully utilized. Consequently, it exists unused resources that are not exploited although they could be used to execute applications compatible with the variable availability of these resources. In this work, we propose a cloud system where the Platform-as-a-Service (PaaS) and Infrastructure-as-a-Service (IaaS) layers interact to find execution trade-offs that exploit the unused resources at IaaS level. PaaS users are involved in the energy optimization by proposing to delay their executions and adapt resource sizes in order to fit with the available unused resources. Our evaluation by simulation is based on real data and expresses a realistic large scale cloud scenario. Results show that according to the proportion of energy-aware users, this system is able to reduce the amount of servers by using resources that would have been wasted otherwise. Therefore, our solution allows datacenters to consume less energy than with usual resource managers where all applications start their execution at submission time with their initial resource size.